CITRA SRIKANDHI DALAM CERITERA MAHABARATA (Pencitraan Nilai -Nilai Kewanitaan dalam Budaya Jawa ) - mamik Widyastuti (Gelar : Jurnal Seni Budaya, 2007)
One of art forms capable for being used as the source of moral values in lift  is Javanese shadow puppet because it contains various kinds of principles and ethic  values. Indonesia people can make use of the principles and values to survive. The  glorious principles and values made use of Indonesian people (espetialIy the Javanese)  have existed since the old days.S rikandhi, one of female figures in the Mahabarata, is often thought of as  an ideal figure because this female figure has the personality that is suitable for a  model for responsibility, discipline, bravery, skills, and leadership. She is willing to  put her own interest a side for the sake of the interest of others or her country.  S rikandhi’s character has the image of  femininity value.Javanese femininity value in the figure of  Srikandhi is different from gender  and feminism at issue which tend to think that Javanese  women are always positioned  as subordinate, weak and hopeless. The figure of Srikandhi projects an image of  femininity value which positions women as strong characters, having strong potential  as resources and not subordinate to men. Gender and feminism at issue aimed at  Javanese women are strongfy rejected   Srikandhi becomes the figure who presents the  rejection of the issue through the estbetic image morally and artistically.Keywords: Srikandhi, Women, Value